KINERJA KAMBING BLIGON YANG DIPELIHARA PETERNAK DI DESA GIRI SEKAR, PANGGANG, GUNUNGKIDUL - Gatot Murdjito; I Gede Suparta Budisatria; Panjono (Panjono); Nono Ngadiyono; Endang Baliarti (Buletin Peternakan, 2011)
This study was conducted to evaluate performances of Bligon goats kept by farmers at Giri Sekar village, Panggang sub-district, Gunungkidul as basic information for establising the village breeding centre program. The research was conducted for three months, starting from October to December 2010, located at Purwo Manunggal farmers’ group, Jerukan, Giri Sekar village, Panggang, Gunungkidul, Yogyakarta. Twenty farmers were involved during the study to be interviewed, while their goats were measured regularly. The parameter of goat meausred in this research were pre weaning, weaning, does and buck. Interviewing the farmers was done using questionnaire. Interview, direct measurement were applied to collect all required informations. The data consisted of farmer’s background, possesion of goats and land, goats’ daily management, service per conception, litter size, post partum estrus, post partum mating, kidding intervals, and average daily gain. Qualitative data were analysed descriptively and presented as percentage, while quantitative data were analysed using Independent Sample T-test, presented as mean and its standard error. The results showed that majority of the farmers (37.9%) kept goat as main sources of income, while others were to saving (34.5%) and produce manure (27.6%). On average, the numbers of goat owned by the farmers was four heads, ranging from 1 to 7 heads. The average of service per conception (S/C), gestation period, litter size, post partum estrus, post partum mating and kidding intervals of Bligon were 1.23; 5.5 months; 1.74 head; 63.2 days; 95 days and 8.53 months, respectively. The average daily gain of male kid, young and adult Bligon goats were 0.15; 0.29and 0.27 kg/head/day, while for female Bligon gotas were 0.16; 0.26 and 0.15 kg/head/day, respectively. It is concluded that performances of Bligon goats was high in terms of litter size, post partum estrus, post partum mating, gestationperiod, kidding intervals and average daily gain.(Keywords: Performance, Bligon goats, Gunungkidul)